Perbandingan Biaya Pelayanan Rawat Inap Peserta BPJS PNS terhadap Peserta PT. Askes PNS di RSUD Semarang Tahun 2022 - Tien Anita Sari; Roro Kushartanti; Endah Widaningtyas (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2023)
The financing of PT ASKES PNS participants in health facilities uses a fee-for-service (FFS) system, where the service provider charges a fee for each action, then ASKES reimburses according to the provisions. However, participants often bear additional costs, especially for VIP treatments. Since January 1, 2014, the National Health Insurance (JKN) program has been implemented with BPJS as the organizer. This study aims to determine the difference in hospitalization rates between BPJS PNS participants and ASKES PNS after policy changes. The research method is in the form of an evaluation survey with a cross sectional approach, using the Independent T-test. The study population was inpatient with indications of typhoid fever. ASKES civil servant data was taken from January to March 2020 as many as 57 patients, while BPJS civil servants January-March 2022 were 72 patients. After the inclusion and exclusion criteria were applied, a final sample of 46 patients was obtained. The results showed that there was a significant difference (p = 0.001) in the average length of stay (ALOS), hospitalization rates, and costs. ALOS ASKES PNS is 4 days, while BPJS PNS is 5 days. The average hospitalization rate for ASKES civil servants is IDR 1,468,124, while BPJS civil servants is IDR 1,494,279. The cost of ASKES civil servant participants is higher (Rp 458,465) than BPJS PNS (Rp 287,889). The conclusion of this study is that there are significant differences in ALOS, tariffs, and fees between ASKES PNS and BPJS PNS. ALOS ASKES is shorter than hospital standards, while BPJS ALOS is according to standards. ASKES hospitalization rates are lower, but the cost is higher. It is recommended that hospitals in the JKN program improve the quality and quality of services.